2003
DOI: 10.1007/s00345-003-0345-0
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of p53 and DNA ploidy following radical prostatectomy

Abstract: This study assesses the correlation of p53 immunoreactivity and DNA ploidy status with biochemical recurrence after radical prostatectomy. p53 protein expression and DNA ploidy were evaluated on 84 archival paraffin-embedded radical prostatectomy specimens. Patients were divided into two groups: those with low (38/84, 45%) and those with high (46/84, 55%) p53 immunoreactivity. The results were correlated with Gleason score, stage and serum PSA. Kaplan-Meier biochemical recurrence free survival and the Cox haza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 18 publications
3
8
0
Order By: Relevance
“…These findings are consistent with previous reports that DNA ploidy adds useful prognostic information for some cancer patients (19,32,42,43). The number of S-Phase cancer cells was reported as an independent predictor of prostate cancer outcome (26).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…These findings are consistent with previous reports that DNA ploidy adds useful prognostic information for some cancer patients (19,32,42,43). The number of S-Phase cancer cells was reported as an independent predictor of prostate cancer outcome (26).…”
Section: Resultssupporting
confidence: 82%
“…The MIB-1 staining index has been associated with PCa patient survival (27,28,33,41). DNA ploidy adds useful prognostic information for some PCa patients (19,32,(42)(43)(44). Our objective was to determine localization patterns of three distinct groups of biomarkers (cathepsin B, cell proliferation: MIB-1 and DNA ploidy) in the prostate needle biopsy sections in the hope of establishing localization similarities (or differences) in biopsy and RP specimens.…”
Section: Discussionmentioning
confidence: 99%
“…Studies evaluating DNA ploidy in prostate cancer have come to varying conclusions. Some studies on 45-850 (mean 139) cancers have suggested a relevant prognostic impact of ploidy (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), while other studies on 33-447 (mean 122) cancers have failed to find significant associations (7,(20)(21)(22)(23)(24). Deletions affecting various chromosomal loci are a hallmark of prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…CIN is frequently reported in prostate cancer specimens (Webb et al, 1996;Zitzelsberger et al, 1996;Deliveliotis et al, 2003) and is thought to be a major event during the transformation of normal prostate epithelium to prostate cancer (Phillips et al, 2001). In addition, significant number of prostate cancer specimens and established cell lines show tetraploidy or near tetraploidy (Webb et al, 1996;Bernardino et al, 1997;Haapala et al, 2001).…”
Section: Discussionmentioning
confidence: 99%